Penggunaan Python Dalam Menyelesaikan Permasalahan Supremum dan Infimum Suatu Himpunan - Fuji Winanti; Annisa Hidayah; Mutia Agustin Purba; Rizky Saputra. T; Novita Atika Sitorus (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This research uses a quantitative approach with the help of Python to solve infimum and supremum problems involving measurements, calculations and data analysis to draw conclusions. This research process consists of several stages: problem identification, modeling a set of numbers or functions, and implementing algorithms in Python to calculate the infimum and supremum. The calculation results are compared with manual analytical solutions to ensure accuracy and efficient use of Python. Sets as a basic concept in programming allow organizing data and logical operations more efficiently. These findings show that Python is not only effective in calculating supremum and infimum, but also speeds up the solution process compared to manual methods. The results of the program execution show that the analyzed set has an infimum fan supremum which is in accordance with the theory, where set 1 has an infimum of 2, set 2 has a supremum of 5, and set 3 has an infimum of 1 and a supremum of 4.